Endothelial vasoactive mediators in young patients with minor heart anomalies - A. V. Yagoda; N. N. Gladkikh (Кардиоваскулярная терапия и профилактика, 2007)
Aim. To investigate regulatory vasoactive mediators – endothelin-1 (ET-1), 6-ketoprostaglandin F1α (6-keto-PGF1α), thromboxane В2 (TXВ2) – in young patients with minor heart anomalies (MHA) and non-differentiated connective tissue dysplasia (CTD). Material and methods. Fifty-three patients, 37 men and 16 women (mean age 22,0±0,8 years) were examined. Plasma concentrations of ТХВ2, 6-keto-PGF1α and ET-1 were measured by immune-enzyme methods. Results. Some specific features of vasoactive mediators in MHA were observed. In patients with three MHA, ET-1 level was increased. In Stage II mitral valve prolapse (MVP), combined with atopic chord (AC) and/or Stage II mitral regurgitation, TXB2 level was increased, without any significant thromboxane-prostacyclin dysbalance. In patients with mixomatous MV degeneration, plasma ET-1 concentration was increased, and TXB2 level was higher than that of 6-keto-PGF1α. Conclusion. In MHA patients, functional endothelial status is disturbed. Disturbance severity is maximal in three MHA and mixomatous MV degeneration.